Navigating Change: A Systematic Analysis of Business Models and Innovation in Indonesia's Event and Decoration Sector - Rolando, Benediktus; Mulyono, Herry; Ingriana, Alberta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The event and decoration industry in Indonesia has experienced significant transformation over the past decade, driven by changing consumer preferences, technological advancements, and growing environmental awareness. As the industry expands and evolves, it faces complex challenges at the intersection of business sustainability, environmental responsibility, and market demands. This qualitative literature review examines these dynamics while focusing on sustainability practices and innovative solutions. This study addresses three key objectives: (1) analyzing operational challenges including environmental sustainability, resource efficiency, and market adaptation; (2) evaluating these challenges' impact on service delivery and customer experience; and (3) developing actionable recommendations for enhancing industry sustainability and innovation. Using a qualitative systematic literature review methodology, the research synthesizes findings from 46 peer-reviewed articles published between 2019-2024, sourced from academic databases including Scopus and Google Scholar . The analysis reveals that the industry faces significant challenges in waste management, sustainable material sourcing, and meeting evolving consumer preferences for eco-friendly services. Key findings highlight the effectiveness of circular economy principles, sustainable design practices, and environmental partnerships in addressing these challenges. The study also identifies how emerging technologies, particularly digital management systems and recycling innovations, can enhance operational efficiency while reducing environmental impact. This research contributes to the growing body of knowledge on sustainable event management practices while providing practical insights for industry stakeholders.